STRATEGI DINAS PENDIDIKAN UNTUK MENINGKATKAN RATA-RATA LAMA SEKOLAH DI KABUPATEN SUMEDANG - Hidayat, Kurnia; Akadun; Safaria, Anne Friday (JRPA - Journal of Regional Public Administration, 2025)
This study aims to analyze the strategies implemented by the Education Office of Sumedang Regency in an effort to increase the Average Length of Schooling (RLS) in the region. RLS is an important indicator that reflects the accessibility and quality of education and has a direct impact on the socio-economic development of the community. The study employs a qualitative approach with a descriptive method, involving policy analysis, in-depth interviews with stakeholders, and a review of relevant literature. The analysis methods used are SWOT to formulate alternative strategies and QSPM to determine priority strategies. The results of the analysis show that the strategies implemented by the Education Office of Sumedang Regency play a crucial role in efforts to increase the Average Length of Schooling (RLS). Various policies and programs focused on improving access to education, developing infrastructure, and enhancing the quality of educators have had a positive impact, although challenges remain to be addressed. The SWOT and QSPM analyses of internal and external environmental factors indicate that the priority strategies for increasing RLS are integrated interventions to raise educational awareness, optimization of educational investment and operations, and improving the quality of educational facilities, infrastructure, and human resources.